2021
DOI: 10.32388/ujr2aw.13
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association of smoking status with SARS-CoV-2 infection, hospitalisation and mortality from COVID-19: A living rapid evidence review with Bayesian meta-analyses (version 11)

Abstract: Aims: To estimate the association of smoking status with rates of i) infection, ii) hospitalisation, iii) disease severity, and iv) mortality from SARS-CoV-2/COVID-19 disease.Design: Living rapid review of observational and experimental studies with random-effects hierarchical Bayesian metaanalyses. Published articles and pre-prints were identified via MEDLINE and medRxiv.Setting: Community or hospital. No restrictions on location.Participants: Adults who received a SARS-CoV-2 test or a COVID-19 diagnosis.Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
9
1
3
Order By: Relevance
“…The prevalence of smokers was quite heterogeneous, ranging from 0% to 70% in Asia, from 0% to 23% in Europe, and from 1% to 35% in the Americas. More importantly, smoking prevalence was systematically lower than adult prevalence estimates observed in countries where the studies were conducted [2]. This suggested that smoking could have a protective role on the incidence of SARS-CoV-2 infection.…”
Section: Silvano Gallusmentioning
confidence: 79%
See 3 more Smart Citations
“…The prevalence of smokers was quite heterogeneous, ranging from 0% to 70% in Asia, from 0% to 23% in Europe, and from 1% to 35% in the Americas. More importantly, smoking prevalence was systematically lower than adult prevalence estimates observed in countries where the studies were conducted [2]. This suggested that smoking could have a protective role on the incidence of SARS-CoV-2 infection.…”
Section: Silvano Gallusmentioning
confidence: 79%
“…È necessario invece basarsi sul crescente numero di studi di coorte che indagano l'incidenza di COVID-19 e che sono condotti sulla popolazione generale. Simons e coll., in una metanalisi -basata su questo tipo di studi e aggiornata a marzo 2021 [2] -hanno mostrato come, rispetto a coloro che non avevano mai fumato, i fumatori hanno un rischio relativo, RR, di 0,71 (intervallo di confidenza, CI, al 95%: 0,61-0,82) e gli ex fumatori di 1,03 (95% CI: 0,95-1,11). Per quanto riguarda invece la gravità e mortalità per COVID-19, ci sono meno dubbi: i fumatori hanno più frequentemente un decorso sfavorevole della malattia rispetto ai non fumatori [3,4].…”
Section: Silvano Gallusunclassified
See 2 more Smart Citations
“…A certain underdetection of cases among smokers could not be ruled out, since they may develop lower antibody levels. 31 However, a recent review concluded that smokers have lower risk of infection, 32 although the mechanisms are not well understood. 33 A lower probability of participation of infected smokers in our study due to their higher risk of hospitalization is unlikely, as we contacted each person up to 3 times -one per round-, so they had several chances to participate.…”
Section: Discussionmentioning
confidence: 99%